Microwave-assisted synthesis of polyfluorenes and their modification to ionomers for proton exchange membranes - Philipp Martschin; Daniela Hirsch; Sebastian Auffarth; Simon Thiele; Jochen Kerres (Materials Today Advances)
Polyaromatics, especially polyphenylenes and their derivates, represent a promising class of materials for electrochemical applications. As they feature no heteroatom in the polymer backbone, such polymers exhibit high chemical, thermal, and mechanical stability. This work demonstrates an approach to speed up the direct arylation polymerization of custom-made polyfluorenes by a microwave-assisted reaction. Modifying respective monomers allows for fine-tuning the polymer properties. Furthermore, our method to functionalize the polymer backbone to an ionomer by microwave-assisted reactions decreased the reaction times by a factor of at least eight. The different positioning of the sulfonic acid functionalization reveals an improved water uptake and conductivity. This approach enables a fast and easy way to accelerate the development of new polyaromatic ionomers for electrochemical applications like fuel cells, electrolyzers, and/or redox flow batteries.